The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/1925863
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Exposures to Hazardous Materials among Nail Cosmeticians in the Kampala City, Uganda

Abstract: Globally, nail salons represent a fast expanding industry and often with low-income cosmeticians. In general, cosmeticians have limited access to safety information about the hazardous materials they handle, which would potentially enable them to minimize workplace exposures. The problem is much pronounced in low- and middle-income countries due to weaknesses in regulation of the industry. We investigated determinants of exposures to hazardous materials among nail cosmeticians in Kampala District, Uganda. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…A majority (70%) of the salon workers were knowledgeable about pathways through which any toxic substances in cosmetics and PCPs enter the body. This finding is consistent, in a general cosmetological context, with that of a study conducted in Uganda on nail cosmeticians [ 12 ], which showed that a majority of nail workers in Kampala City were knowledgeable about potential harms from hazardous materials contained in nail care products.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A majority (70%) of the salon workers were knowledgeable about pathways through which any toxic substances in cosmetics and PCPs enter the body. This finding is consistent, in a general cosmetological context, with that of a study conducted in Uganda on nail cosmeticians [ 12 ], which showed that a majority of nail workers in Kampala City were knowledgeable about potential harms from hazardous materials contained in nail care products.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of risks associated with occupational exposure to cosmetics and PCPs, a majority (88%) of the salon workers were aware that occupational exposure to cosmetics and PCPs can cause ill health. Previous studies that have reported comparably high levels of knowledge have attributed it to workplace training of salon workers [ 12 , 18 ]. In this study, the role of workplace training on knowledge of risks associated with occupational exposure to cosmetics and PCPs was not investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The informal sector salons and technicians, however, procure products that are readily available and affordable, and which might contain banned and unsafe chemicals. This practice was reported in a study in Uganda where nail salons used cheap cosmetics to keep costs low (23).…”
Section: Introductionmentioning
confidence: 82%